Study of Cross Sections for 10 Li 10 Reaction From Cross Sections of Li a,n) Reaction Using the Reciprocity Theory for the Ground State - Youhana, H. M.; Sarsam, M. N.; Ebrahiem, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, light elements Li ,10B for (a,n) and (n,a) reactions as well as o-particle energy from threshold energy to 10 MeV are used according to the available data of reaction cross sections. The more recent cross sections data of (a,n) and (n,a) reactions are reproduced in fine steps 42 Kev for 10B(n,o) Li in the specified energy range, as well as cross section (o,n) Values were derived from the published data of (n,a) as a function of a-energy in the same fine energy steps by using the principle inverse reactions. This calculation involves only the ground state of Li OB in the reactions ’Li(a,n) B B (n,a) Li Introduction When two charged nuclei overcome their Coulomb repulsion, a rearrangement of the constituents of the nucleus may occur. Similar to the rearrangement of atoms in reacting molecules during a chemical reaction this may result a a nuclear reaction target Nuclear reactions are usually produced by bombarding a or nucleus with a nuclear projectile in most cases a nucleon (neutron proton) or a light nucleus such as a deuteron or an majority of nuclear At low excitation energies 10 MeV),the reactions involve the formation of two nuclei one nearly equal in charge and mass number to the target nucleus. Such reactions are represented by an equation of the type b X a the lab. System) Where X target (at rest in bombarding particle